Extension practices in School and Educational Psychology in Basic Education: an experience report - da Silva, Natan Daniel; Pinto da Silva, Ana Claudia; Fagundes Rodrigues, Carlos Eduardo; Müller, Vanessa; Schultz Danzmann, Pâmela; Nunes Rodrigues, Cristian; Dapieve Patias, Naiana (Guará Journal, 2025)
The objective is to report and discuss extension practices carried out in the field of School and Educational Psychology, developed with students and teachers from two basic education school institutions located in Rio Grande do Sul. The method used is the experience report, and the data presented were analyzed with the aid of the Iramuteq software. As results, actions aimed at promoting psychoeducation and anxiety management strategies with elementary school students from a public school are reported, as well as fostering reflections and the sharing of experiences on psychosocial well-being among elementary school teachers from a private school. It is discussed that the developed activities enabled reflections, learning, and the exchange of experiences on themes related to mental health in school environments. It is understood that the development of extension practices in School and Educational Psychology contributes to the promotion of well-being and quality of life within school communities, as well as to academic and professional training in Psychology.